2008
DOI: 10.1007/s11136-008-9430-6
|View full text |Cite
|
Sign up to set email alerts
|

The applications of PROs in clinical practice: what are they, do they work, and why?

Abstract: Future research needs to identify ways in with PROs can be better incorporated into the routine care of patients by combining qualitative and quantitative methods and adopting appropriate trial designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
421
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(433 citation statements)
references
References 76 publications
4
421
1
7
Order By: Relevance
“…A recent review identified that screening using PROs often leads to an increased detection rate of problems by clinicians but is rarely followed up by interventions or associated with an improvement of patient symptoms [18]. This may be due to the fit of the intervention in clinical practice as well as the attitude of clinicians to the use of quality of life measures for decision making [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review identified that screening using PROs often leads to an increased detection rate of problems by clinicians but is rarely followed up by interventions or associated with an improvement of patient symptoms [18]. This may be due to the fit of the intervention in clinical practice as well as the attitude of clinicians to the use of quality of life measures for decision making [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for efficacy is mixed possibly due to the complexity of the intervention which involves not only sound PROs but also training on interpretation of scores and management guidelines for staff [1]. In the United States, guidelines and national initiatives have been published to promote assessment and management of supportive care needs of cancer patients including psychological, social and spiritual concerns [2].…”
Section: Introductionmentioning
confidence: 99%
“…PROMs have been used in research -as outcomes in clinical trials and economic evaluations -for many years (Appleby et al, 2004;Fung and Hays, 2008;Greenhalgh, 2008;Marshall et al, 2006;Rose and Bezjak, 2009;Snyder and Aaronson, 2009) and have recently migrated into everyday clinical practice (Appleby and Devlin, 2005;Black, 2013;Fung and Hays, 2008;Rothwell et al, 2010;Snyder and Aaronson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is currently accepted that it should also include the patient's perspective, which can be obtained with the use of patient-reported outcome measures (PROMs). There is evidence that PROMs enable the clinician to better judge patients' problems, because they provide a means to gain insight into the way patients perceive their health and the impact treatments have on their quality of life, and this will help in choosing the most suitable management for their condition [1].…”
Section: Introductionmentioning
confidence: 99%